The Yersinia pseudotuberculosis Cpx envelope stress system contributes to transcriptional activation of rovM. Issue 1 (1st January 2019) - Thanikkal, Edvin J.; Gahlot, Dharmender K.; Liu, Junfa; Fredriksson Sundbom, Marcus; Gurung, Jyoti M.; Ruuth, Kristina; Francis, Monika K.; Obi, Ikenna R.; Thompson, Karl M.; Chen, Shiyun; Dersch, Petra; Francis, Matthew S.
ABSTRACT: The Gram-negative enteropathogen Yersinia pseudotuberculosis possesses a number of regulatory systems that detect cell envelope damage caused by noxious extracytoplasmic stresses. The CpxA sensor kinase and CpxR response regulator two-component regulatory system is one such pathway. Active Cpx signalling upregulates various factors designed to repair and restore cell envelope integrity. Concomitantly, this pathway also down-regulates key determinants of virulence. In Yersinia, cpxA deletion accumulates high levels of phosphorylated CpxR (CpxR P). Accumulated CpxR P directly repressed rovA expression and this limited expression of virulence-associated processes. A second transcriptional regulator, RovM, also negatively regulates rovA expression in response to nutrient stress. Hence, this study aimed to determine if CpxR P can influence rovA expression through control of RovM levels. We determined that the active CpxR P isoform bound to the promoter of rovM and directly induced its expression, which naturally associated with a concurrent reduction in rovA expression. Site-directed mutagenesis of the CpxR P binding sequence in the rovM promoter region desensitised rovM expression to CpxR P. These data suggest that accumulated CpxR P inversely manipulates the levels of two global transcriptional regulators, RovA and RovM, and this would be expected to have considerable influence on Yersinia pathophysiology and metabolism.